The Use of Traditional and Modern Tools for Monitoring Wetlands Biodiversity in Africa: Challenges and Opportunities - Stephenson, P. J.; Ntiamoa-Baidu, Yaa; Simaika, John P. (Frontiers in Environmental Science, 2020)
Biodiversity is being lost in wetlands at a faster rate than any other biome. Effective conservation and management of wetlands biodiversity requires data on species status and threats to inform decision-making. However, there are key challenges in Africa around the availability, usability and quality of data, willingness to use data, and capacity. We review these challenges, using examples from Ramsar sites and other wetlands across the continent, and propose solutions to help information users access high quality data in the right format at the right time. We assess the relevance of traditional monitoring methods, as well as innovative new tools such as remote sensing and environmental DNA. We conclude by explaining how governments, civil society and the private sector can enhance data collection by applying common, policy-relevant indicators, scaling up the application of traditional and appropriate new tools and protocols, building capacity in key institutions, and using partnerships and credible science-policy interfaces. Only by sharing and upscaling the solutions to data collection and use will we be able to mainstream biodiversity into decision-making and ultimately stop biodiversity loss across African wetlands.